Quantitative Comparison of Algorithms for Estimating the Air-sea Exchange of Carbon Dioxide in Malacca Straits - Lilik Maslukah; Didi Adisaputro; Widodo Setiyo Pranowo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
A precise quantification of the sea surface partial pressure of carbon dioxide (pCO2(water)) at the water surface is required in order to define the role of the sea in air-sea exchange of CO2. Even though the pCO2(water) can be measured directly, the semi-empirical model has seen numerous application in determining the pCO2 (water) due to a time-and cost-efficient. This study aims to compare the pCO2 and FCO2 (Flux of CO2) calculated using Zhai and Zhu algorithm with the underway datasets of pCO2 obtained during the scientific cruise of CISKA-SPICE III in April 2013. The partial pressure of CO2 (pCO2) was measured using a high-accuracy electrochemical instrumentation underway HydroC/CO2 FT (flow through) with an error ±1 μ atm. Furthermore, in order to calculate the pCO2 and the FCO2 employing widely used algorithms, some data were needed including wind speed, sea surface temperature and chlorophyll-a extracted from MODIS (Moderate Resolution Imaging Spectroradiometer). According to the results obtained, the difference between the pCO2 and FCO2 derived from those two algorithms are significant. The underway datasets of pCO2 are ranging from 409.52-544.01 µatm. Meanwhile, the pCO2 derived using the Zhai algorithm and Zhu algorithm are between 405.003–422.79 µatm and 398.94-752.06 µatm respectively. The FCO2 are varied between 0.02–0.06 molC.m-2.day-1 (Zhai algorithm), 0.02-0.57 molC.m-2.day-1  (Zhu algorithm) dan 0.04-0.23 molC.m-2.day-1 (the underway datasets). A comparison of the two results reveals that pCO2 derived using Zhai algorithm is closer with the underway datasets compared with the result of pCO2 calculated using Zhu algorithm with the MRE (Mean Relative Estimation Error) as large as 19.4% and 39% respectively. Taken together, these results suggest that the Zhai algorithm is more appropriate to determine algorithms for estimating the air-sea exchange of carbon dioxide in the Malacca Straits.Keywords: carbon dioxide, Malacca Straits, pCO2, FCO2, Zhai and Zhu algorithm